ANALISIS PERBEDAAN PENGARUH PENGGUNAAN VINYL DAN KARPET SEBAGAI PENUTUP LANTAI TERHADAP KENYAMANAN TERMAL PADA KAMAR HOTEL (Studi Kasus : Hotel Grasia Semarang) - Amelia Luisa; Seli Astriani; Muhammad Mukhlisin; Sutarno Sutarno (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
Replacing the floor covering from carpet with vinyl is an effort to increase the comfort of room users and the effectiveness of carrying out maintenance. However, the use of vinyl and carpet as floor coverings for hotel rooms has an influence on thermal comfort. So it is necessary to analyze the effect of using vinyl and carpet as floor coverings on thermal comfort in hotel rooms. The research method used is descriptive quantitative. This research is in the form of measuring temperature, humidity, and lighting in rooms 204, 206, 222, and 224 Hotel Grasia Semarang. Rooms with vinyl floor coverings tend to be comfortable in the morning (-0,5 ≤ PMV value ≤ +0,5), during the day the thermal comfort can worsen (if PMV value ≤ -0,5 or PMV value ≥ +0,5), and in the afternoon tend to be comfortable. While rooms with carpet floor coverings in the morning tend to be comfortable, during the day